Sleep and delinquency: The context of self-control, social support, and sex differences among French adolescents - Semenza, Daniel C. (European journal of criminology, 2023)
Prior research demonstrates that poor sleep is an important predictor of delinquent behavior among adolescents. Engagement in delinquency is linked to a range of negative mental and physical health outcomes over the life course, underscoring a critical need to address adolescent sleep problems to reduce delinquency. However, little scholarly attention has been paid to how the broader context of social support influences the sleep?delinquency relationship. In this study, we analyze a series of structural equation models using a sample of 447 French adolescents to examine how parental and peer support correspond to three related aspects of sleep among adolescents (quantity, quality, and the frequency of sleep disturbance) with implications for delinquency. Furthermore, we assess how sex differences moderate the relationship between social support and sleep. First, we find that all three indicators of sleep are associated with delinquency, significantly mediated by reductions in self-control. Second, both peer and parental support correspond to sleep outcomes with full sequential mediation evident for sleep quality and delinquency. Finally, we find significant differences in the relationship between social support and all sleep indicators for boys and girls. Peer support is more strongly associated with sleep among boys, whereas parental support is more strongly associated with sleep among girls. We discuss the implications of these findings for improving adolescent sleep to reduce delinquency as well as opportunities for future research.